Scaffolded Reading Instruction of Content-Area Texts - Fisher, Douglas; Frey, Nancy (The Reading teacher, 2014)
In this column, we focus on increasing text complexity during scaffolded, small group instruction. We begin with a discussion about the need to adjust expectations for leveled texts for older readers and then focus on the ways in which teachers can accomplish this.